МОДЕЛИРОВАНИЕ ЭВОЛЮЦИИ ТЕРМОАБРАЗИОННОГО БЕРЕГА - Леонтьев И.О. (My University, 2003)
Evolution of thermal abrasion coast is simulated by analogy with sedimentary coast erosion, but taking into account additional losses of material due to thermodynamic phenomena. The net contribution from the latter to the sediment budget is presented as excess sediment input from the coastal zone (q T). With such an approach, the problem amounts to determination of storm-induced changes in coast profile and quantitative estimate of q T. The first task is solved using the author's model of sedimentary coast evolution. The thermodynamic constituent q T is estimated from empirical data on thermal erosion of the East Siberian Sea coasts. The q T value is supposed to be bounded by saturation limit controlled by both local climatic parameters and the cliff height. The model seems to be in good agreement with available data. It has been also used to predict thermal-abrasion cliffs evolution in the Laptev and East Siberian seas for the next 100 years with regard for global warming. The results suggest the rate of cliff recession to increase by 40-50% in the second half of the century as compared to the present-day.
Keywords: 551.435.36-551.4.013